2005
DOI: 10.1111/j.1742-4658.2005.05052.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural mutation by deletion of Lys9 in the thrombin A‐chain affects the pKa value of catalytic residues, the overall enzyme's stability and conformational transitions linked to Na+ binding

Abstract: Recently, a homozygous deletion mutation of one of the two contiguous Lys9 ⁄ Lys10 residues in the A-chain of a-thrombin (DK9) was identified in patients with severe prothrombin deficiency and hemorrhagic diathesis [1,2].Compared with the wild-type (WT) form, the specificity constants of hydrolysis by DK9 of the synthetic substrate d-Phe-Pip-Arg-pNA and fibrinopeptide A were found to be 18-and 60-fold lower, respectively. The catalytic competence of the natural thrombin mutant with deletion of the Lys9 residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 20 publications
(58 reference statements)
1
26
0
Order By: Relevance
“…Notably, the perturbed structure produced by modeling contains features documented in the X-ray crystal structure of the inactive form of thrombin E* [25]. Recent measurements of the pKa of the catalytic His57 further support a direct effect on active site residues [10]. Our study shows that the K9A and K10A mutants have functional properties comparable to those of wild type.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Notably, the perturbed structure produced by modeling contains features documented in the X-ray crystal structure of the inactive form of thrombin E* [25]. Recent measurements of the pKa of the catalytic His57 further support a direct effect on active site residues [10]. Our study shows that the K9A and K10A mutants have functional properties comparable to those of wild type.…”
Section: Resultssupporting
confidence: 55%
“…Deletion of Lys9 in the A chain is associated with a bleeding phenotype [8]. The thrombin mutant ΔK9 shows defects in the activation of its zymogen form [9], but the mature enzyme features impaired Na + binding and significantly reduced activity toward a chromogenic substrate, fibrinogen, PAR1 and protein C [9] due to long-range perturbation of the active site moiety and catalytic triad [9,10]. These findings underscore the importance of the A chain in thrombin function and warrant a thorough analysis in terms of mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Other naturally mutations, like deletion of K9 or K10 (Akhavan et al, 2000), are also associated with severe bleeding. Interestingly, the defect causes impaired fibrinogen and PAR1 cleavage, reduced response to Na + activation (De Cristofaro et al, 2004, and long-range perturbation of active site residues (De Cristofaro et al, 2006). The A chain is rich in charged residues that make polar interactions with partners of the B chain.…”
Section: Thrombin Structurementioning
confidence: 99%
“…The authors suggested that hypoprothrombinemia is caused by the incomplete folding of the A-chain, which is then unable to stabilize the B-chain structure. Two recent studies on the Lys301 deletion prothrombin mutant have suggested that A-chain structure affects the conformation and catalytic properties of thrombin through long range allosteric effects on the active site and insertion loops [25, 26]. Interestingly, a recent crystal structure of thrombin complexed with sulfo-hirudin found that Lys301 participates in a divalent metal binding site between the heavy and light chains of thrombin [27].…”
Section: Naturally Occurring Mutations In Human Prothrombinmentioning
confidence: 99%